The Canadian criminal code offence of trafficking in persons: challenges from the field and within the law - Kaye, Julie (2015)
Despite early ratification of the United Nations Trafficking in Persons Protocol, the Criminal Code offence of trafficking in persons in Canada has received little analytical or interpretive attention to date. Adopted in 2005, this offence has resulted in successful convictions in a limited number of cases and criminal justice authorities have continued to rely on alternate or complementary charges in cases of human trafficking. In particular, prosecutions for cases involving non-sexual labour trafficking remain extremely low. This article provides a socio-legal examination of why the offence of trafficking in persons in Canada is under-utilized in labour trafficking cases. Based on an analysis of data generated from 56 one-on-one interviews gathered from a variety of actors involved in counter trafficking response mechanisms and a legal examination of the key components of the offence, we argue that definitional challenges have resulted in narrow understandings and problematic int